Population size and time since island isolation determine genetic diversity loss in insular frog populations. Issue 3 (February 2014) - Wang, Supen; Zhu, Wei; Gao, Xu; Li, Xianping; Yan, Shaofei; Liu, Xuan; Yang, Ji; Gao, Zengxiang; Li, Yiming
Abstract Understanding the factors that contribute to loss of genetic diversity in fragmented populations is crucial for conservation measurements. Land‐bridge archipelagoes offer ideal model systems for identifying the long‐term effects of these factors on genetic variations in wild populations. In this study, we used nine microsatellite markers to quantify genetic diversity and differentiation of 810 pond frogs (Pelophylax nigromaculatus) from 24 islands of the Zhoushan Archipelago and three sites on nearby mainland China and estimated the effects of the island area, population size, time since island isolation, distance to the mainland and distance to the nearest larger island on reduced genetic diversity of insular populations. The mainland populations displayed higher genetic diversity than insular populations. Genetic differentiations and no obvious gene flow were detected among the frog populations on the islands. Hierarchical partitioning analysis showed that only time since island isolation (square‐root‐transformed) and population size (log‐transformed) significantly contributed to insular genetic diversity. These results suggest that decreased genetic diversity and genetic differentiations among insular populations may have been caused by random genetic drift following isolation by rising sea levels during the Holocene. The results provide strong evidence for a relationship between retained genetic diversity and population size and time since island isolation for pond frogs on the islands, consistent with the prediction of the neutral theory for finite populations. Our study highlights the importance of the size and estimated isolation time of populations in understanding the mechanisms of genetic diversity loss and differentiation in fragmented wild populations.